Literary fortifications : Rousseau, Laclos, Sade - DeJean, Joan E. (Princeton University Press, 1984)
This highly original interpretation of the novel of the French Classical age explores military strategy as a central metaphor in Rousseau's Julie and Emile, Laclos' Les Liaisons dangereuses, and Sade's Les 120 Journees de Sodome. Originally published in 1984. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.